PERUBAHAN BUDAYA BATOBO PADA ERA MODERNISASI DI DESA SIMANDOLAK KECAMATAN BENAI KABUPATEN KUANTAN SINGINGI - Rahmad Alfindo; Basri " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This research was conducted in the Simandolak village Benai subdistrict, Kuantan Singing regency. the purpose of this study is the first to determine the cause of the change in the modernization batobo cultural in the Simandolak Benai, district of Kuantan Singingi. the second objective is to determine the impact of cultural change batobo in the simandolak village benai district of Kuantan Singingi. Analyzing the data in this research use descriptive quantitative research methods. This quantitative descriptive research method is an analysis that seeks to provide a detailed picture based on facts found in the field and presented in the form of descriptions and assisted with the calculation of numbers, percentages, and tables. This quantitative descriptive study is presented in the form of descriptions and assisted with the calculation of numbers, percentages, and tables as well and is also supported by data to support the primary and secondary data exist. with the inclusion of the modernization to batobo cultural impact of cultural changes that occurred in the batobo. where, it can be seen that in the of cultural modernization batobo the use of technology both in the activities of plowing paddy fields and also a change in the tools people used a food to be brought to the fields by Simandolak villages. Field study results show that there is the occurrence of significant changes in the cultural tradition batobo which is perceived by the people in the Simandolak villages, even the traditions that have been there since the former activities cultural traditions batobo already started to disappear. This is caused by some of the effects that influence the changes that occur in cultural traditions batobo namely the impact of positive and negative impacts.Keyword : Change, Culture, Batobo